2023
DOI: 10.1186/s40001-023-00990-2
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis, pathophysiology and preventive strategies for cardiac surgery-associated acute kidney injury: a narrative review

Abstract: Acute kidney injury (AKI) is a common and serious complication of cardiac surgery and is associated with increased mortality and morbidity, accompanied by a substantial economic burden. The pathogenesis of cardiac surgery-associated acute kidney injury (CSA-AKI) is multifactorial and complex, with a variety of pathophysiological theories. In addition to the existing diagnostic criteria, the exploration and validation of biomarkers is the focus of research in the field of CSA-AKI diagnosis. Prevention remains t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 157 publications
(173 reference statements)
0
10
0
Order By: Relevance
“…Intraoperative ischemic injury is mainly related to hemodynamic instability, involving patient activities, changes in infusion rates, administration of new drugs, venous/arterial catheterization for monitoring, fluid infusion, anesthesia induction, mechanical ventilation, and other factors that may induce hypotension. [24,25] Several meta-analyses have explored the diagnostic value of numerous biomarkers for AKI. For instance, Ho et al reported that KIM-1 demonstrated the highest predictive value for postoperative AKI (AUROC, 0.72), which aligns with our study findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intraoperative ischemic injury is mainly related to hemodynamic instability, involving patient activities, changes in infusion rates, administration of new drugs, venous/arterial catheterization for monitoring, fluid infusion, anesthesia induction, mechanical ventilation, and other factors that may induce hypotension. [24,25] Several meta-analyses have explored the diagnostic value of numerous biomarkers for AKI. For instance, Ho et al reported that KIM-1 demonstrated the highest predictive value for postoperative AKI (AUROC, 0.72), which aligns with our study findings.…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative ischemic injury is mainly related to hemodynamic instability, involving patient activities, changes in infusion rates, administration of new drugs, venous/arterial catheterization for monitoring, fluid infusion, anesthesia induction, mechanical ventilation, and other factors that may induce hypotension. [ 24 , 25 ]…”
Section: Discussionmentioning
confidence: 99%
“…In the case of fluid excess, hemofiltration should also be targeted to provide an adequate fluid balance in the post-CPB period. Intraoperative hypovolemia should be avoided though, as it has a proven detrimental impact on kidney function [115,116]. A further significant benefit of hemofiltration during the CPB is osmotic load and metabolite removal.…”
Section: Fluid Balance and Osmotic Regulationmentioning
confidence: 99%
“…[3] Moreover, AKI has become a major public health problem in the world. [4] More than 2 million heart surgeries are performed worldwide each year [5] ,The incidence of acute renal injury (CSA-AKI) after cardiac surgery is as high as 40%, which is the main cause of AKI, and about 3% of patients need at least temporary renal replacement therapy (RRT). [6] Therefore, early screening of CS-AKI patients will help to reduce perioperative mortality, reduce ICU hospitalization days, and reduce medical expenses.…”
Section: Introductionmentioning
confidence: 99%